2015
DOI: 10.1039/c5ra09022a
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature Au induced crystallization of titanium dioxide thin films for resistive switching applications

Abstract: Metal induced decrease of crystallization temperature of sol-gel derived titanium dioxide (TiO 2 ) thin films is reported. It is shown that the Au induced onset of crystallization occurs at a temperature of 250 C as compared to 400 C when it is deposited directly on the same substrate. The crystallization process is probed using X-ray diffraction and confirmed by Raman spectroscopy. The onset of crystallization is evidenced by the appearance of the diffraction peak from the (101) plane of anatase TiO 2 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Another well-known method to decrease the temperature of crystallization is metal-induced crystallization, 18−21 which was applied to titania materials by Sangani et al in 2015. 22 This report showed a reduction of the crystallization temperature from 400 to 300 °C through the diffusion of gold species through a vitreous titania film. To our knowledge, no one has yet reported coupling metal-induced crystallization with microwave-assisted crystallization.…”
Section: ■ Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Another well-known method to decrease the temperature of crystallization is metal-induced crystallization, 18−21 which was applied to titania materials by Sangani et al in 2015. 22 This report showed a reduction of the crystallization temperature from 400 to 300 °C through the diffusion of gold species through a vitreous titania film. To our knowledge, no one has yet reported coupling metal-induced crystallization with microwave-assisted crystallization.…”
Section: ■ Introductionmentioning
confidence: 79%
“…This burst of crystallization differs from what has been observed in TiO 2 films via convective heating metal-induced crystallization. In this report by Sangani et al, crystallization centers appeared in a mass of amorphous titania. The difference in mechanism may be explained by the inhomogeneous distribution of Au in the TiO 2 film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of crystallization of thin films using a gold layer was studied via Raman imaging and showed that very small and sparse crystallites appear at 250 °C. 27 The density of crystallites increases with annealing temperature; it seems that the crystallites do not grow in size, but rather, more small crystallites nucleate within the film. Yang et al 27 found that, when TiO 2 was deposited on a thin contact film, Ni and Cu participated in the MIC to a higher degree than Au and NiO contact films.…”
Section: Mechanism Of Metal-induced Crystallization In Titaniamentioning
confidence: 99%
“…The relative amount of anatase formation in the final material is higher for the samples anodized with a higher voltage compared to the TiO 2 nanotubes anodized at a lower voltage [ 38 ]. Sangani et al [ 39 ] demonstrated that the addition of metals, such as Au, to the sol–gel derived TiO 2 thin films also decreases the crystallization temperatures. Elevated temperatures are, however, responsible for the atoms’ rearrangements in a TiO 2 lattice.…”
Section: Crystallization Processmentioning
confidence: 99%